(3bhi GdCOhjI GdeaQOI dLGdjfhSs - (3Mfjf Hf ESMGb , CHh RjO Mfjf Hf ESMGb GdYHGOj,J (B260 (3g` s ((3gHI Gddg GdESQGFjdi s)
(3ChdgG (B:s
(3bGd LGdjfhS (B: (3dSJ CMJGL Cf CHjf gGgfG eHdZ GdEfJaGY HeYQaI bhi GdCOhjI ai JQcjH s
(3BNQgG (B:s
(3BNQ GdebGdI GdMGOjI fMf gPG GdeGfhf ai eOGhGI GdbQhM GdeJYafI GdMGOKI ai Gdae s
(3fSNI hKjbIs
(3JHUQI GdYfhGf (B:s
(3JQLeI (B/ (3fbd s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B287 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B87s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B205 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B146 s
Keywords: (3GdWHs